Differences between cancer patients and others who use medicinal Cannabis. - Matthew M Cousins; Mary Jannausch; Reshma Jagsi; Mark Ilgen (PLoS ONE, 2021)
Background Cancer patients have been at the forefront of policy discussions leading to legalization of medical Cannabis (marijuana). Unfortunately, Cannabis use among those with cancer is poorly understood. Methods A diverse group of patients seeking certification for medical Cannabis in the state of Michigan were surveyed at the time of their presentation to medical dispensaries. The survey assessed demographics, employment/disability, pain, physical functioning, mental health, mode of Cannabis use, and frequency/amount of Cannabis use. Chi-square and t-tests were performed to compare those who did and did not endorse cancer diagnosis. Results Analysis of data from 1485 adults pursuing medical Cannabis certification, including 72 (4.8%) reporting a cancer diagnosis, indicated that those with cancer were older [mean age 53.4 years (SD = 10.5) vs. 44.7 years (SD = 13.0); p<0.001] than those without cancer. They also differed regarding employment status (p<0.001; working: 20.8% vs. 46.2%; disabled: 44.4% vs. 26.5% for those with vs. those without cancer, respectively). Those with cancer used less Cannabis (p = 0.033 for quantity used) and used Cannabis less often (p = 0.032 for frequency of use); they less frequently endorsed smoking Cannabis (80% vs 91%; p = 0.015). There was a non-significant trend to increased edible use in those with cancer (57% vs. 44%; p = 0.052). Conclusions Patients with cancer who are seeking medical Cannabis are different from those seeking medical Cannabis without cancer, and they report using Cannabis differently. Further research to characterize the patterns and consequences of Cannabis use in cancer patients is needed.